FBI‐1 inhibits epithelial‐to‐mesenchymal transition, migration, and invasion in lung adenocarcinoma A549 cells by downregulating transforming growth factor‐β1 signaling pathway. Issue 3 (5th January 2022) - Lim, Wonchul; Jeon, Bu‐Nam; Kim, Young‐Joo; Kim, Ki‐Hwan; Ko, Hyeonseok
Abstract: The factor binding inducer of short transcripts‐1 (FBI‐1) is a POZ‐domain Kruppel‐like (POK) family of transcription factors and is known as a proto‐oncogene or tumor suppressor in various carcinomas. However, the role of FBI‐1 on epithelial‐to‐mesenchymal transition (EMT) and invasiveness in lung cancer remains unknown. Preliminarily, clinical data such as tissue microarray, Kaplan−Meier, and Oncomine were analyzed to confirm the correlation between lung cancer metastasis and FBI‐1. To investigate the function of FBI‐1 in EMT in lung cancer, EMT was measured in FBI‐1‐deficient or FBI‐1‐overexpressing cells. FBI‐1 showed decreased expression in tumors metastasized to lymph nodes than in the primary tumor. In addition, it was also associated with improved survival rates of lung cancer patients. FBI‐1 knockdown improved E‐to‐N‐cadherin switching, migration, and invasion in A549 cells, similar to the initiation of EMT stimulated by transforming growth factor‐ β1 (TGF‐β1). In contrast, overexpression of FBI‐1 inhibited the transcription and activation of Smad2, thereby interfering with EMT, despite stimulation by TGF‐β1. These results suggest that FBI‐1 plays a negative role in EMT in lung cancer via the TGF‐β1 signaling pathway, implying its use as a new potential therapeutic target and diagnostic indicator for early stage of lung cancer metastasis.